Tinjauan Ekonomi Islam terhadap Gapoktan Sugihwaras Jombang - Ilyas, Ilyas Nurul Azam; Susi, Susi Fatmawati (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2025)
The agricultural sector is one of the important factors in social life, because agriculture produces the food needed by the community. Food is a basic need as well as being the essence of human life, therefore the right to food is a very important part of human rights. Economic empowerment in farmer group associations is very important for farmer groups to increase knowledge and information about agriculture, especially in order to make farmers creative, innovative, and independent. The purpose of the study was to find out about the practice of empowering farmer groups in Sugihwaras Village, Ngoro District, Jombang Regency in the agricultural sector, to find out about strategies for improving and developing farmers through farmer group associations in Sugihwaras Village, Ngoro District, Jombang Regency. The method used in this research is qualitative, where the author collects data that is in fact, analyzes the data, interprets the data, and supports to answer the problems studied by the author so that the authors get conclusions based on analyzing the data. The results of this study can be concluded that with the empowerment program that has been implemented by Gapoktan, there have been many improvements in the fields of cooperation, fulfillment of economic and health needs, increased income, and participation in development. a concept where the concept uses the principles, Tawhid, Ta'awun or help, and justice. Where the three principles are a concept that can form a member's welfare in carrying out an activity that is being carried out. With this value to protect the function from external threats, namely morality, morality is a human attitude in behaving